FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SDM PADA SEKRETARIAT DAERAH KABUPATEN INDRAGIRI HILIR - jurnalmap map; Ratna Dewi; Hadi Susanto; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to describe the effect of work motivation, work discipline, and organizational climate on employee performance at the Regional Secretariat of the Indragiri Hilir Regency. The study population included all employees of the Regional Secretariat of Indragiri Hilir Regency, totaling 184 people and a sample of 65 people with an analysis unit in the form of employees. The results showed that partially work motivation, work discipline, and organizational climate significantly influence employee performance. But the dominant influence on employee performance is work discipline. Simultaneously work motivation, work discipline, and organizational climate influence employee performance. Organizational goals will be easily achieved if the organization can motivate, discipline, and create a healthy organizational climate and encourage employee performance such as implementing a performance-based reward system and comfortable and healthy working conditions.